2015
DOI: 10.1890/es14-00314.1
|View full text |Cite
|
Sign up to set email alerts
|

Linking northern fur seal dive behavior to environmental variables in the eastern Bering Sea

Abstract: Abstract. Northern fur seals (Callorhinus ursinus) breeding on the Pribilof Islands, Alaska have declined dramatically over the past 40 years. Effective conservation of northern fur seals depends on understanding the foraging behavior of adult females whose foraging success is linked to pup survival. We determined the foraging behavior for 11 tagged lactating female northern fur seals from the Pribilof Islands using a statespace modeling approach with an autoregressive movement model. To interpret at-sea behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…, , Joy et al. , Russell et al. ), these data sources cannot be used for inferences about different types of resting or foraging behavior.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…, , Joy et al. , Russell et al. ), these data sources cannot be used for inferences about different types of resting or foraging behavior.…”
Section: Introductionmentioning
confidence: 99%
“…, Isojunno and Miller , Joy et al. , Russell et al. ) or as covariates in state transition probabilities (e.g., Morales et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oceanographic conditions are known to be correlated with foraging, health, maternal investment, and reproductive success in pinnipeds. Studies have shown that other otariids, primarily fur seals, associate with certain frontal features while foraging or migrating (Joy et al, 2015; Ream et al, 2005; Speakman et al, 2020; Sterling et al, 2014), but few studies have linked these features to demography. Existing examples include correlations between sea ice and recruitment in Weddell seals (Hadley et al, 2007), SSTs and first‐year survival for subantarctic fur seals ( Arctocephalus tropicalis ; Beauplet et al, 2005), and El Niño conditions and first‐year survival in southern elephant seals ( Mirounga leonina ; McMahon & Burton, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for top predators that inhabit vast and heterogenous landscapes, where there is often a mismatch between the ecological question and the data that are available to examine the relevant hypotheses (Conn et al, 2014). Pinnipeds exhibit a range of responses to oceanographic variability, including changes in body condition, reproductive output, maternal attendance patterns, diet, the timing of pupping or weaning, foraging effort, and levels of stranding and mortality (Joy et al, 2015; Speakman et al, 2020; Sterling et al, 2014). While it is important to study these relationships at the scale that is most relevant to the species or ecological process of interest, this is often difficult or impossible to do (Mannocci et al, 2017; Wiens, 1989).…”
Section: Introductionmentioning
confidence: 99%